The old age in Polish and American series - ANIOŁ, JOANNA; KORONKIEWICZ, KAJA; SOKOŁOWSKA, EDYTA (Journal of Education Culture and Society, 2020)
The educational and socialization role of the media is not the latest novelty, however there are niches that have not been developed yet. Realizing the opinion-forming role of the mass media, which may be reflected in social behaviours, the authors of this article will analyse the content of chosen media products. The image of elderly people presented by the most popular Polish and American series will be examined. The research aims to find whether Desperate Housewives and Colours of happiness (original title: Barwy szczęścia) adjust the image of old age to the social-demographic situation, which is constantly changing in the majority of countries. Does the colossus – television promote stereotypes which make age discrimination morally approved – or just the opposite – a well thought out image, shaping the recognition and respect for people in their “third age”?